KEPEMIMPINAN TRANSFORMASIONAL KEPALA SEKOLAH MEMODERASI PENGARUH KOMPETENSI DAN EFIKASI DIRI TERHADAP KINERJA GURU SMP DI KECAMATAN TAMBAKROMO KABUPATEN PATI - Effendhi, Aziz; Srimindarti, Ceacilia (Jurnal Ilmiah Telaah Manajemen, 2018)
This study aimed to examine the influences of competence and self-efficacy on teacher's performance of SMP Tambakromo Pati with moderated by transformational leadership. The usefulness of this research is to explain and extend previous research on transformational leadership role to moderate influences competence and self-efficacy on teacher's performance. This study uses population of 120 teachers of Junior High School in Tambakromo district of Pati regency. The analysis technique used is the quasi regression model of moderation. Based on the results can be concluded that: teacher's competence influences on teacher's performance, teacher's self-efficacy influences on teacher's performance, transformational leadership of headmaster influences on teacher's performance, transformational leadership of headmaster strengthening the influences of teacher's competence on teacher's performance, transformational leadership of headmaster is strengthen the influences of teacher's self-efficacy on teacher's performance. Keywords: competence, self-efficacy, transformational leadership, performance